Brokerage and Closure: An Introduction to Social CapitalBrokerage and Closure: An Introduction to Social Capital, by BurtRonald S. Oxford: Oxford University Press, 2005. - Johnson, Jonathan L. (Academy of Management Review, 2006)
The article reviews the book ?Brokerage and Closure: An Introduction to Social Capital,? by Ronald S. Burt.